ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF KOMODITAS KENTANG DAN KUBIS DI WONOSOBO JAWA TENGAH - SAPTANA -; SUMARYANTO -; SUPENA FRIYATNO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2003)
The Agricultural Development in Indonesia is focused to enhance thestructure of production that more diversified through sustainable agribusinessapproach. With this context, based on the demand side horticulture commoditiesespecially potato and cabbage are feasible to developed by increasing of productionarea, cropping intensity, and productivity. This paper is proposed to: (a) conductingfinancial and economic analysis of both commodities, (b) comparative andcompetitive analysis, (c) measuring the divergences and government policy impact,(d) formulating the incentive policy interim of both commodities development. ByPolicy Analysis Matrix (PAM) method, the result showed that both commoditieshave comparative and competitive advantage, which is indicated by DRC and PCRless then 1 .The calculation showed the DRC for potato is arranging 0.239 – 0.306and for cabbage is 0.622-0.660. PCR for potato is arranging 0.413-0.468 and forcabbage is 0.854-0.875. That mean for producing the one unit value added of bothcommodities can be achieved by using less then one unit of the domestic resourcefactors. In other word, in Wonosobo Central Java both commodities are moreprofitable to produce than import.